Responding to new Imageries in African indigenous Spiritualties - Nweke, Kizito Chinedu (UIN Sunan Gunung Djati Bandung, 2022)
As a result of rash and incorrect assumptions, African spiritualities have been adulterated, bastardized, and multiplied. Academic studies in African spiritualities